Pengaruh Proses Rekrutmen dan Seleksi terhadap Kualitas Karyawan Baru: Mediasi Kompetensi Karyawan pada PT LGP Banjarmasin - Fauziannor Fauziannor; Yudi Rahman; Nonni Yap (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This research aims to analyze the influence of the recruitment and selection process on the quality of new employees through the mediation of employee competency at PT LGP Banjarmasin. The research method used is quantitative with data collection techniques through distributing questionnaires to 85 respondents who are new employees recruited in the 2023–2025 period. The data analysis technique uses Partial Least Square Structural Equation Modeling (PLS-SEM). The research results show that the recruitment and selection process has a positive and significant effect on the quality of new employees. In addition, employee competency has been proven to be able to significantly mediate the relationship between the recruitment and selection process and the quality of new employees. These findings confirm that the implementation of systematic, objective and competency-based recruitment and selection procedures can increase the effectiveness of workforce placement and have an impact on improving the quality of the company's human resources. Thus, this research recommends that PT LGP Banjarmasin continue to strengthen the competency-based selection process to obtain employees who suit the organization's needs.